A case of an unfortunate tooth fairy visit to a ventilator‐dependent child. Issue 6 (8th April 2022) - Be'er, Moria; Amirav, Israel; Cahal, Michal; Rochman, Mika; DeRowe, Ari; Lavie, Moran
Abstract: An 8‐year‐old boy recently sustained a cerebellar arteriovenous malformation rupture, and subsequently suffered from severe neurological injury and became ventilator‐dependent through a tracheostomy. During a routine clinic visit, the parents reported that a loose baby tooth had fallen out and disappeared 7 days earlier. The physical examination was unremarkable, but a chest X‐ray demonstrated a foreign body in the left lung and secondary atelectasis. A rigid bronchoscopy extracted what turned out to be a tooth from the left lower lobe bronchus, with no associated sequelae. Aspiration of a tooth is rare, and it is mostly seen in children and elderly patients following trauma, endotracheal intubation, and dental procedures. Only a few previous studies emphasized the increased risk of foreign body aspiration among neurological impaired children. This unique report describes a child in his physiological exfoliation period, which is characterized by the spontaneous shedding of 20 teeth over the course of several years. In severely neurologically impaired children, this period carries a risk of aspiration of teeth and secondary pulmonary damage. Therefore, treating physicians and caregivers must be aware of this risk, and routine dental check‐ups are advised in a neurological impaired child during this period.